2022
DOI: 10.1111/all.15506
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world evidence for the long‐term effect of allergen immunotherapy: Current status on database‐derived European studies

Abstract: Randomized controlled trials (RCTs) are the gold‐standard for benefit–risk assessments during drug approval processes. Real‐word data (RWD) and the resulting real‐world evidence (RWE) are becoming increasingly important for assessing the effectiveness of drug products after marketing authorization showing how RCT results are transferred into real life care. The effectiveness of allergen immunotherapy (AIT) has been assessed in several RWE studies based on large prescription databases. We performed a literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 62 publications
(410 reference statements)
1
22
0
2
Order By: Relevance
“…Real-world research evidence is increasingly important for evaluating post-marketing effectiveness of drugs, which is the practice of translating the results of randomised controlled trials into real-world clinical applications. 23 Patients enrolled in randomised controlled trials are highly selected with a variety of demanding conditions, for which are not comparable to more heterogeneous populations in clinical practice. 24 Our real-world research included a number of patients with variable treatment patterns and various alternative interventions in practice, which could better reflect the real efficacy of Azvudine for the management of hospitalised patients with COVID-19 and pre-existing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world research evidence is increasingly important for evaluating post-marketing effectiveness of drugs, which is the practice of translating the results of randomised controlled trials into real-world clinical applications. 23 Patients enrolled in randomised controlled trials are highly selected with a variety of demanding conditions, for which are not comparable to more heterogeneous populations in clinical practice. 24 Our real-world research included a number of patients with variable treatment patterns and various alternative interventions in practice, which could better reflect the real efficacy of Azvudine for the management of hospitalised patients with COVID-19 and pre-existing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…RCTs have shown that AIT is effective in reducing allergy symptoms, and RWD-based studies have provided evidence that these benefits can extend to the long term and in diverse patient groups. [105][106][107][108] Additionally, in patients with concurrent asthma, AIT was associated with a reduced likelihood of asthma exacerbations and pneumonia. 109 RWD of persistence and adherence rates showed for SCIT and SLIT significant variability depending on the study methodology and duration of follow-up.…”
Section: Ne W Me Thodology For Clini C Al Re S E Archmentioning
confidence: 99%
“…[63][64][65] SCIT and SLIT have been proven to effectively reduce symptoms and medication use and modify disease pathology, leading to a long-term curative effect after stopping treatment. [66][67][68] AIT relies on the modifying effect on innate and adaptive immune responses associated with type 2 inflammation. 69,70 The effects of AIT on innate responses include reducing the local infiltration of mast cells, basophils, and eosinophils; decreasing circulating frequencies of ILC2; elevating complement C1Q-expressing regulatory DCs; and restoring epithelial cell integrity.…”
Section: Aitmentioning
confidence: 99%
“…AIT can be applied subcutaneously (SCIT) or sublingually (SLIT) and is suitable for children and adults for a variety of allergens, including pollen, cat, dog, house dust mite, and venom 63–65 . SCIT and SLIT have been proven to effectively reduce symptoms and medication use and modify disease pathology, leading to a long‐term curative effect after stopping treatment 66–68 . AIT relies on the modifying effect on innate and adaptive immune responses associated with type 2 inflammation 69,70 .…”
Section: Treatment Strategies For Armentioning
confidence: 99%